Application of Augmented Reality-Based Solar System Recognition Using Metaverse Studio - Izza Wildan Ridhoni; Muhammad Sholeh (International Journal of Applied Sciences and Smart Technologies, 2023)
Learning media is currently developing with various innovations, especially in utilizing information technology. One of the technologies used for the learning process is Augmented Reality (AR). The purpose of the research is to provide alternative learning media using information technology, especially focusing on the use of AR. The learning that will be developed in this case is learning aimed at children to introduce learning about the solar system using interactive AR. The content of the learning media developed includes several things, namely learning the solar system and quizzes to test children's knowledge about the solar system. The research method used in developing learning media uses the Research and Development (RD) method. The application development process can be done by adding features. The results of this study produce an AR-based application that describes learning the solar system in 2D/3D form and is equipped with a quiz to train children's knowledge.